Contrasting delivery modes for second screen TV content—Push or pull?. Issue 129 (September 2019) - Brown, Andy; Aizpurua, Amaia; Jay, Caroline; Evans, Michael; Glancy, Maxine; Harper, Simon
Highlights: We studied two modes for presenting companion content to TV: push and pull. We analysed the distribution of visual attention for both delivery modes. We examined the cognitive workload of viewers in both cases. We explored viewers preferences about each companion content mode. We presented a list of recommendations for the design of companion content apps. Abstract: The use of mobile devices during television viewing is now commonplace, and broadcasters are increasingly supplying programme-related 'companion content'. To produce an optimal user experience, it is important to determine how the delivery of companion content affects and is perceived by the viewer — without this we risk distracting the viewer, leading to frustration and disengagement. We present a controlled study investigating how attention, cognitive load (as measured by the NASA TLX), and users' preferences are affected by the provision of two different content delivery modes: pushed and pulled . We find that delivery mode affected the temporal distribution of gaze to the tablet, with a consistent viewing pattern for pushed updates, which attracted attention within a few seconds, and a more diverse set of viewing patterns when updates were pulled. Cognitive load was similar in both conditions, and there was no consensus as to which mode was preferred, but users showed strong, polarised individual preferences. The advantages of each delivery mode are presented as a set of recommendations for the delivery of companion content.